PENGARUH NON DEBT TAX SHIELD DAN DIVIDEND PAYOUT RATIO TERHADAP PENGGUNAAN HUTANG (Studi empiris pada perusahaan manufaktur yang go public di Bursa Efek Indonesia tahun 2010-2012) - Enny Yulia Natasari; Indira Januarti (Diponegoro Journal of Accounting, 2014)
This study aims to analyze and provide empirical evidence about the effect of non debt tax shield and dividend payout ratio on debt using. Several previous studies showed varying results. To obtain valid results, then doing a test on each variable based on the hypothesis constructed. The samples used were selected by purposive sampling method. A population was 148 manufacturing companies listed in Indonesia Stock Exchange. After reduced with some criteria, 34 companies identified as samples. Observation period was 2010 to 2012, so the total number of sample used was 102 samples. Multiple regressions were used to examine the hypothesis. The results indicate that non debt tax shield is significantly affect the debt using. On the other side, dividend payout ratio has no effect on the debt using.